IMPACT OF TIME OF ARTIFICIAL INSEMINATION ON CONCEPTION RATE IN INDIAN YAK - BORAH, B K D; DEKA, B C; BISWAS, R K; DEORI, S; CHAKRAVARTY, P; SINHA, S; AHMED, K (The Indian Journal of Animal Reproduction, 2022)
The female yaks (n=52) were detected in estrus by parading vasectomized bull between 8-9 am (morning) and between 3-4 pm (evening). A group of females (n=18) detected in estrus in morning were inseminated twice on the same day between 9-10 am and between 4-5 pm. The remaining females (n=13) detected in estrus in morning were inseminated once on the same day between 4-5 pm. Further, the females detected in estrus in evening were either inseminated twice (n=13) i.e. on the same day between 4-5 pm and next day between 9-10 am (n=18), or were inseminated once (n=8) on following day between 9-10 am. In all the groups, an almost similar (p>0.05) conception rate was recorded between 53.8 to 62.5%. In brief, it may be concluded that if estrus is detected in Indian yak either in the morning or in the evening, a single insemination may be done in the afternoon of same day or in the morning of following day, respectively.